Designing A Prototype of Observation and Intervention Applications for Intensive Care Unit (ICU) Patients at Sultan Imanuddin Pangkalan Bun Hospital - Aimandinata; Sentot Imam Suprapto; Ratna Wardani (Universitas STRADA Indonesia, 2025)
Background: The use of Information Technology (IT) for storing and retrieving patient data has advantages over paper, but faces challenges such as infrastructure problems, information technology, lack of needs assessment, cultural barriers, and high costs for software, hardware, and data exchange standards. Purpose: Research was conducted to explore the design of a prototype observation and intervention application for Intensive Care Unit (ICU) patients at Sultan Imanuddin Pangkalan Bun Regional Hospital. Methods: The design of this research is qualitative research with a phenomenological approach with the focus of the research directed at exploring the design of a prototype application for observation and intervention for Intensive Care Unit (ICU) patients at Sultan Imanuddin Hospital Pangkalan Bun. Apart from that, with a qualitative approach. The informants in this research were the owners or people in charge of the clinic, a total of 6 (six) people with triangulation of sources. Results: The observation and intervention application in the ICU at Sultan Imanuddin Hospital aims to improve communication, reporting and quality of patient service, as well as increasing data accuracy. The main obstacles are network problems and adjusting application usage. Technical solutions, better network infrastructure, medical staff training and hospital support are needed. The main goal is reporting efficiency in emergency situations and rapid response to changes in the condition of ICU patients. Conclusion: The Sultan Imanuddin Hospital ICU application aims to improve patient communication and reporting, but there are network problems and adjustments to the use of the application that need to be addressed.